OPTIMASI FORUM DISKUSI ONLINE DALAM PEMBELAJARAN PAI: STUDI KASUS PENGGUNAAN PLATFORM E-LEARNING DI UNIVERSITAS NURUL JADID PROBOLINGGO - M Mahbubi; Yuni Rifqiyah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to examine the optimization of online discussion forums in Islamic Religious Education (PAI) at Universitas Nurul Jadid Probolinggo. Online discussion forums, as part of e-learning platforms, hold significant potential for enhancing student engagement and interaction in learning. However, student participation in these forums remains low, which may reduce the effectiveness of the learning process. This research employs a qualitative approach with a case study design to explore the experiences of students and lecturers using online discussion forums. Data were collected through in-depth interviews, observation of forum activities, and content analysis of the discussion materials. Thematic analysis was used to identify factors influencing student participation from the perspectives of students, lecturers, and the technology used. This study aims to provide practical recommendations for lecturers and e-learning platform managers to improve the use of discussion forums as tools to deepen students’ understanding of PAI material. Additionally, it contributes to the broader development of online learning in higher education by encouraging increased student participation in technology-based learning.